Пути снижения частоты развития и степени тяжести алиментарно-энтерогенного вегетативного синдрома после гастрэктомии - Олексенко, В.В. (Таврический медико-биологический вестник, 2013)
Ефективність нового варіанту гастропластики у профілактиці розвитку і зниження ступеня тяжкості алиментарно-ентерогенного вегетативного синдрому досліджено серед 189 хворих раком шлунка які перенесли гастректомію. Основну групу склали 88 хворих, яким у ході реконструктивного етапу гастректомії, був сформований резервуар для прийнятої їжі в початковому відділі тонкої кишки, у контрольну групу увійшов 101 пацієнт з традиційним петльовим способом реконструкції. При зіставленні клініко-біохімічних показників у віддалені терміни спостережень встановлено, що застосування нового варіанту гастропластики дозволяє вже в перший рік після гастректомії скоротити частоту розвитку гиперглікемічного синдрому з 20,2% до 12,7%, гіпоглікемічного синдрому з 13,9% до 9,8%, у другий рік після операції з 19,6% до 13,6% і з 13,7% до 9,1%, на третій рік з 20,8% до 9,5% і з 12,5% до 4,7% відповідно синдромів. При цьому, важка форма прояви алиментарно-ентерогенного вегетативного синдрому діагностована через 1 рік у 2,5% хворих, а через 2 роки у 3,9% хворих з традиційним петльовим способом реконструкції, серед пацієнтів основної групи, у всі терміни спостережень, не було зареєстровано. We have developed a new method of forming a reservoir of food intake in the initial jejunum (Ukraine Patent number 50082), with a loop variant reconstruction of digestive tract, giving it a range of special features to ensure deposition of food and its initial processing. Studied 189 patients with gastric cancer - 109 (57,7%) men and 80 (42,3%) of women aged 27 to 80 years (59,7 ± 8,56) years. A study group included 88 patients - 51 (57,9%) male and 37 (42,0%) of women 60,4±6,87 years that when performing gastrectomy, during the reconstruction phase gastroplasty, in the initial jejunum was formed tank to food intake. The control group consisted of 101 patients - 58 (57,4%) men and 43 (42,6%) females 59,1±5,78 years, who used traditional loop technique gastroplasty. When comparing the clinico-biochemical indices in long-term observations revealed that the application of the new version of the gastroplasty allows already in the first year after gastrectomy reduce the frequency of hypoglycemic syndrome from 20,2% to 12,7%, hipoglycemic syndrome from 13,9% to 9,8%, in the second year after the operation from 19,6% to 13,6% from 13,7% to 9,1%, in the third year from 20,8% to 9,5% from 12,5% to 4,7%, respectively syndromes. In this case, a severe form of nutrition-enterogenous vegetative syndrome diagnosed in 1 year at 2,5% of patients, and after 2 years from 3,9% of the patients with the traditional loop method of reconstruction, among the patients of the group, over the whole period of observations, has been recorded.